Analyzing Spatial Factors in Crime-inducing Culture in Chaloos - Noghlehbari, Mohammad Hossein Omidi (Journal of History Culture and Art Research, 2017)
Feelings of security in urban areas are one of the qualitative criteria of living space. With the rise in urbanization and increasing abnormal urban behavior, especially offenses, this issue has become of great importance. This study aims to identify and analyze the effects of spatial factors on crime-inducing culture in affluent and non-affluent neighborhoods of Chaloos. The method used in this study is analytical-descriptive and it is practical in terms of objective. In order to study and understand the status of physical-spatial structures of affluent and non-affluent neighborhoods in Chaloos, we used field study method. Data were collected through interview, notes taking and questionnaire. The results indicate that in affluent neighborhoods, all criteria components of spatial differences are above the mean (Mean=3), but in non-affluent neighborhoods, all components are lower than the mean. In addition, there is a significant relationship between criteria components of spatial differences and the formation of crime-inducing culture (except the diagnosis component) in the affluent and non-affluent neighborhoods.